Genetic association analysis of polymorphisms in four cytochrome P450 genes, the MDR1 gene and treatment-outcome in Xhosa schizophrenia patients - Truter, Erika (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Genetics))--University of Stellenbosch, 2007.